2018
DOI: 10.1097/iae.0000000000001897
|View full text |Cite
|
Sign up to set email alerts
|

Preferred Retinal Locus Locations in Age-Related Macular Degeneration

Abstract: The clinical PRL evaluation methodology that we describe can be used to facilitate making decisions on how to provide best visual rehabilitation to patients with a central scotoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…Sunness et al described a series of patients in which 90 per cent of Stargardt disease patients had loci in the inferior field and 63 per cent of patients with age‐related macular degeneration had a left field fixation locus. In another series, 29.2 per cent were nasal followed by temporal, superior and inferior . This series showed preference for superior locus.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Sunness et al described a series of patients in which 90 per cent of Stargardt disease patients had loci in the inferior field and 63 per cent of patients with age‐related macular degeneration had a left field fixation locus. In another series, 29.2 per cent were nasal followed by temporal, superior and inferior . This series showed preference for superior locus.…”
Section: Discussionmentioning
confidence: 83%
“…Patients with central scotoma have a strong tendency to develop a PRL in the left side of the visual field . However, the loci in other locations are also beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…These results seemed reasonable from a functional standpoint and agreed with previous studies. 20,[27][28][29][30][31] Field defects below fixation may interfere with many visual tasks that require information from the inferior visual field, such as walking, reading, and writing. The tendency for the visual system to locate visual field defects to the right of fixation was expected.…”
Section: Discussionmentioning
confidence: 99%
“…In the inhibition group, the PRL was temporal or nasal to the scotoma (38%). Finally, Erbezci and Ozturk 50 reported that the most frequent location of the PRL in the retina was nasal, or in the left visual field.…”
Section: Binocular Fixational Control In Patients With Macular Diseasementioning
confidence: 98%